Leakage analysis and leakage monitoring system design for LNG tanker filling process - Lei Song; Tao Yin; Chuanjun Han; Hai Zhao (Scientific Reports, 2024)
Abstract During the filling process of LNG tank trucks, due to the long-term operation of filling equipment in low temperature and high-pressure conditions, the sealing parts in the equipment are prone to failure, leading to leaks. The reasons for the leakage of LNG filling equipment were analyzed, and the diffusion of LNG after different equivalent leakage hole diameters and different wind speeds were numerically analyzed. A gas leak monitoring system suitable for LNG filling stations was established based on TDLAS technology. The analysis results show that when the equivalent leakage hole diameter is greater than 4 mm, the height of natural gas diffusion will exceed 5 m within 2 s without wind; the concentration of natural gas above the leakage point is inversely proportional to the height, and the decrease in concentration at a height of 5 m is between 50% and 60% compared with a height of 0.5 m; the wind will bend the natural gas diffusion shape downwind, and the degree of bending decreases as the equivalent leakage hole diameter increases; the optimal laser incidence angle of the laser gas sensor is between 30° and 50°, and the theoretical effective monitoring area width of the sensor when the installation height is 5 m is 4.46 m within the optimal laser incidence angle range.